Intrapericardial teratoma in a newborn: a case report - Oto, Öztekin; Güzeloğlu, Mehmet; Kır, Mustafa; Metin, Kivanç; Çakmakçı, Handan; Albayrak, Gökhan; Koç, Aydın (The Turkish Journal of Pediatrics, 2012)
We report a successfully surgically intervened case of intrapericardial teratoma, which was diagnosed prenatally. Intrapericardial teratomas are rare cases, and surgical management of those tumors are challenging in this age group. The compression effect of the mass led to misdiagnosis of the anomaly as a transposition of the great vessels. We conclude that intrauterine echocardiography in experienced hands is an essential tool for the follow-up of these patients to detect the pericardial effusion and compression of the cardiac structures, which may cause tamponade and heart failure.